1991
DOI: 10.2176/nmc.31.1023
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Cerebrospinal Gliomatosis

Abstract: A 65-year-old male was admitted with memory and gait disturbance. A computed tomography (CT) scan showed bilateral, diffuse, low-density areas with two round, slightly enhanced masses. T1-weighted magnetic resonance image revealed a low-intensity area in the left paraventricular region, which converted to increased signal intensity, extending to the right paraventricular region through the splenium, on T2-weighted images. The tumor was diagnosed as glioblastoma multiforme after needle biopsy and treated by irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In the present case, neoplastic cells infiltrated cerebrum, brainstem and cerebellum but no changes were observed in the spinal cord. GC with spinal cord invasion has been occasionally reported in human medicine 19,20 as well as in one out of the six canine cases studied by Porter et al 3 Besides, in human cases of GC a typical finding is the widening of the white matter tracts (particularly the corpus callosum and posterior limb of the internal capsule) 21 . In the present case, an enlargement of the affected hemisphere was observed.…”
Section: Discussionmentioning
confidence: 95%
“…In the present case, neoplastic cells infiltrated cerebrum, brainstem and cerebellum but no changes were observed in the spinal cord. GC with spinal cord invasion has been occasionally reported in human medicine 19,20 as well as in one out of the six canine cases studied by Porter et al 3 Besides, in human cases of GC a typical finding is the widening of the white matter tracts (particularly the corpus callosum and posterior limb of the internal capsule) 21 . In the present case, an enlargement of the affected hemisphere was observed.…”
Section: Discussionmentioning
confidence: 95%
“…Nevin [ 16], Moore [ 17], Kawano et al [20], Yamamoto et al [28], Schmidbauer et al [31], Sarhaddi et al [34] and Ferraro et al [50] reported cases with spinal involvement. Sarhaddi et al [34] reported a case of spinal astrogliosis without neoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Kawano et al, 18 Yamamoto et al, 19 Schmidbauer et al, 20 Ferraro et al, 21 Finally, inconclusive symptoms, noninformatory laboratory data, nonspecific changes on CT, and the usual isointense to hypointense images on T1-and diffuse high signal intensity on T2-weighted images on MRI -in at least two, but often three lobes of the brain with extension into the…”
Section: If the Final Destination For The Clinician Is Diagnosis Difmentioning
confidence: 99%